Removal of Iron in Groundwater Using Marble Column Filter - Ling Xin, Khong (International Journal of Integrated Engineering, 2019)
Water shortage during dry season has become a big issue affecting the daily activities of the public as well as the worldâ€™s attention. The potential of groundwater as a secondary water source can ease the situation of water shortage since the current water supply comes from surface water. However, groundwater pollution is inevitable because of human induced and natural occurrence. Therefore, this project studies to overcome excessive iron from the groundwater using marble in pebble size based on previous studies of calcium carbonate and sand size is in this study. Both sizes are compared to investigate the highest efficiency in removing iron without chemical use. The filtration is run with 4 different flow rates which are 0.017 ls-1, 0.011 ls-1, 0.008 ls-1 and 0.007 Â ls-1. The highest removal percentage of iron, 93.83% is for the sand size marble column filter when the flow rate is 0.007 ls-1. The marble is possible to be a cheap and effective filter media for iron removal in development of groundwater pre-treatment.